Association between trace metals exposure and hearing loss - Peixi Zou; Menghuan Li; Wei Chen; Junfeng Ji; Fei Xue; Zhiyi Wang; Li Xu; You Cheng (Frontiers Media S.A., 2022)
BackgroundTrace metals have side-effect on human health. The association between trace metals exposure and hearing loss remains unclear.MethodsA total of 8,128 participants were exacted for analysis of association between trace metals and hearing loss from the database of the National Health and Nutrition Examination Survey (NHANES) (2013-2018). Multivariable logistic regression and restricted cubic spline models were used to examine the association between trace metals and hearing loss.ResultsParticipants with hearing loss had a higher level of lead, cadmium, molybdenum, tin, thallium, and tungsten (all p < 0.05). After adjusting for confounders, compared with the reference of the lowest quartile, the ORs with 95%CIs for hearing loss across quartiles were 1.14 (0.86, 1.51), 1.49 (1.12, 1.98), 1.32 (0.97, 1.80) for cobalt, and 1.35 (0.98, 1.87), 1.58 (1.15, 2.16), 1.75 (1.28, 2.40) for tin. Individuals with the level of cobalt at third quartile had 49% higher risks of hearing loss than those at lowest quartile. And participants with highest quartile of tin had 1.75-folds risks of hearing loss than those with lowest quartile of tin. There were increasing trends in risks of hearing loss with a raised level of thallium (p for trend <0.05). Restricted cubic spline regression analysis indicated that there was a nonlinear association between hearing loss and the levels of tin (p for nonlinearity = 0.021). Subgroup analysis showed that individuals of female, without hypertension and diabetes, and with a higher level of low-density lipoprotein cholesterol had modified effects on the associations between hearing loss and exposure to tin.ConclusionsOur study indicated that exposure to cobalt and tin were significantly associated with hearing loss.